Pengaruh Model Problem Based Learning Terhadap Kemampuan Menulis Materi Teks Negosiasi Oleh Siswa Kelas X Sma Negeri 1 Kutalimbaru Tahun Pembelajaran 2023/2024 - Savera Tri Divioya Saragih; Elly Prihasti Wuriyani (Morfologi : Jurnal Ilmu Pendidikan, Bahasa, Sastra dan Budaya, 2024)
The problem with this study is that many schoolchildren still complain about having trouble writing essays, texts, or stories. The issue with writing skills is that for students to write well, they also need a lot of extensive knowledge. The objective is to determine the effect of the problem-based learning model on the ability of class X students at SMA Negeri 1 Kutalimbaru to write negotiation text material for the 2023–2024 academic year. This will be done by measuring students' ability to write negotiation text material using class problem-based learning. This exploration technique is trial research. A scoring system for evaluating a person's capacity to write negotiation texts serves as the data collection method. The examination area is at SMA Negeri 1 Kutalimbaru. The information examination methods in this exploration are homogeneity test, ordinariness test and t test. Based on the calculations, this study came to the conclusion that, at the 95% significance level, or = 0.05, tcount is 38.39 and ttable is 1.66. The research alternative hypothesis (Ha) is accepted because tcount is greater than ttable (38.39 is greater than 1.66). Therefore, the ability of class X students at SMA Negeri 1 Kutalimbaru to write negotiation texts is influenced by the problem-based learning model.